Improving solid waste management practices in the Ashanti Akim North District of the Ashanti Region - Asamoah, Frederick Danquah (2011)
A thesis submitted to the Board of Postgraduate Studies of the Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfillment of the requirements for the Award of Master of Science Degree in Health Education and Promotion.